Temperature controller with microprocessor for incubators of newborns. - Pérez Ruíz, J.; Rodriguez, G.; Lezama Flores, E.; Rodríguez, M. (Revista Mexicana de Ingenieria Biomedica, 2018)
A temperature controller (CONTEMP-DZ) for infant incubators is presented based on a previously designed general purpose microcomputer (MIC-DZ). The controller has the following operating characteristics: Two operating modes (servo or normal), five alarm functions, numerical temperature display, a temporary alarm inhibitor, temperature control range: 25.5 to 39.9 degrees Celsius, resolution: + - 0.2 degrees Celsius.